Optimization of Biogas Production from POME mixed with Indigenous Inoculum using Two-Stage Anaerobic Reactor Operating at Mesophilic Temperature, Coupled with Nanomembrane Separator - Malcolm Mussen, Lamoh (Universiti Malaysia Sarawak (UNIMAS), 2020)
The broad objective of this research is to optimize biogas production from Palm Oil Mill Effluent (POME) by reducing Chemical Oxygen Demand, Biological Oxygen Demand and sludge levels in high-strength POME before disposal in order to assuage its negative impacts on environment, economy and health. The COD and VSS of POME would be converted by microorganisms to reusable resources such as biogas, potable water and organic sludge for achieving social, economic and environmental sustainability. The novelty of this research is to develop a model by using Central Composite Design (CCD) combined with Design of Experiment (DOE) to optimize the number of experiments in a double stage fermentation process. Based on the findings of literature review, five important process factors such as HRT, C/N, SRT, pH, OLR were identified with their limits of input to digestion process. The limit of each factor was analysed by CCD and DOE to determine steps of experiment and number of experimental runs for finding the significant factors and their respective optimum values relating to optimum level of biogas production from POME. Two-stage fermentation was used to separate and accelerate acidogenesis and methanogenesis in five sets of 5-litre CSTR reactors for POME digestion to produce biogas. Fifty (50) experimental runs as per CCD and DOE software outputs were needed to determine optimum level of inputs in developing the model for optimal biogas production. The experiment revealed that the factors significantly (p<0.05) affect biogas production are HRT, SRT, pH and OLR; but C/N has also contributed to produce biogas though its contribution was not significant (p>0.05). The experiment also unlocked the information related to optimum value of factors that contributed to optimize biogas production. Based on the 3D plots of Response Surface Methodology (RSM), the optimum value for OLR is 5 kg/m3/d, pH is 6.6–7.1, C/N is 30.5, HRT is 6.5 days and SRT is 13.5 days with optimum output of biogas production at 3.0 L/d. This finding has been validated using similar experiments with two 350 L CSTR reactors whose results demonstrated that an empirical model built to estimate biogas production from POME appeared quite fit to predict output of anaerobic reactor within the 5% error limit.